2018
DOI: 10.1080/21645515.2018.1508624
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD20 monoclonal antibodies: reviewing a revolution

Abstract: Since the inception of rituximab in the 1990s, anti-CD20 monoclonal antibodies have revolutionised the treatment of B cell hematological malignancies and have become a cornerstone of modern gold-standard practice. Additionally, the potent efficacy of these agents in depleting the B cell compartment has been used in the management of a broad array of autoimmune diseases. Multiple iterations of these agents have been investigated and are routinely used in clinical practice. In this review, we will discuss the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 252 publications
(239 reference statements)
1
75
0
Order By: Relevance
“…4 a Natural killer- (NK-) cells (CD56 bright CD16 + ) and T helper -cell subsets in rituximab (RTX) treated MS vs. RRMS without RTX, and healthy controls [4]. b Regulatory T-cells (CD4 + CD25 + FoxP3 + ), c Th1-cells (CD4 + IFNγ + ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 a Natural killer- (NK-) cells (CD56 bright CD16 + ) and T helper -cell subsets in rituximab (RTX) treated MS vs. RRMS without RTX, and healthy controls [4]. b Regulatory T-cells (CD4 + CD25 + FoxP3 + ), c Th1-cells (CD4 + IFNγ + ) …”
Section: Resultsmentioning
confidence: 99%
“…There is growing evidence for the efficacy of B-cell depleting therapies in various autoimmune diseases [ 4 ]. This has previously resulted in the FDA approval of RTX for the treatment of rheumatoid arthritis in 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 shows examples of therapeutic Abs for treating human diseases. Therapeutic Abs have had enormous success, exemplified by Rituximab (an anti-CD20 MAb), which is the first therapeutic MAb for treating lymphoma and used for treatment of several autoimmune diseases [112]. Other notable examples are recombinant MAbs to tumour necrosis factor, TNF, and programmed death-1, PD-1, used for treating rheumatoid arthritis and malignant melanoma, respectively [74,75].…”
Section: Recombinant Antibodiesmentioning
confidence: 99%
“…122 This drug was initially used to treat lymphomas but currently is being used for the treatment of certain autoimmune diseases. 123 The effect of rituximab results from its regulatory effect on the cell cycle, including apoptosis stimulation, complement-dependent B cell lysis, and antibody-dependent cell-mediated cytotoxicity. 124 Recent studies showed that rituximab not only affects B cells but has another possible mechanism of action against CD20 + T cells in MS patients, 125 or in EAE mice.…”
Section: Rituximab Effects On the Chemokines And Chemokine Receptorsmentioning
confidence: 99%